2019
DOI: 10.15174/au.2019.2306
|View full text |Cite
|
Sign up to set email alerts
|

Producción y cambios morfológicos de Pennisetum ciliare cv. H-17 en función de la edad de rebrote y altura de pradera

Abstract: Se evaluó la producción de materia seca (MS) y composición morfológica en función de la edad de rebrote (ER; cuatro, seis y ocho semanas) y altura de pradera (AP) en Pennisetum ciliare cv. H-17, durante época de lluvias (ELL) y seca (ES). Las variables fueron MS total (MSTT), hoja (MSh), tallo (MSt), material muerto (MSmm) y AP. Se utilizó un diseño completamente al azar con cuatro repeticiones y análisis de regresión lineal. Durante ELL, la MSTT fue similar (p > 0.05) entre ER (8342 kg ha-1) y disminuyó 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Victoria–Monterrey highway, municipality of Güémez, Tamaulipas; 23°56′26.5″N, 99°05′59.9″W, at 193 masl (INEGI, ). The climate is classified as BS1 (h’)hw (García, ); where there are two well‐defined periods, the maximum (May–October) and minimum (November–April) rainfall (Garay‐Martínez et al, ; Gómez et al, ). The soil is 66% clay with no salinity problems (RAS = 0.19), alkaline pH (8.3), with 4.27% and 0.25% content of organic matter and nitrogen, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Victoria–Monterrey highway, municipality of Güémez, Tamaulipas; 23°56′26.5″N, 99°05′59.9″W, at 193 masl (INEGI, ). The climate is classified as BS1 (h’)hw (García, ); where there are two well‐defined periods, the maximum (May–October) and minimum (November–April) rainfall (Garay‐Martínez et al, ; Gómez et al, ). The soil is 66% clay with no salinity problems (RAS = 0.19), alkaline pH (8.3), with 4.27% and 0.25% content of organic matter and nitrogen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This decreased the paddock coefficient from 12 to 4 ha/AU (Hanselka, ) while the nutritional value of the forage was increased with crude protein (CP) contents from 7% to 13% (Saini, Jain, & Joshi, ), and drought tolerance was improved. Under rainfed conditions, the annual dry matter (DM) yields reached up to 9 t/ha (Garay‐Martínez et al, , ), supporting an animal load of 1.8 AU ha/year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El AFE disminuye al incrementar la edad de rebrote y se relaciona con la dureza y grosor de las hojas (Garay et al, 2019). En este estudio AFE mantuvo un comportamiento similar entre tratamientos, pero los valores más altos se observaron con 150 kg.…”
Section: Tasas De Crecimientounclassified
“…The height of the meadow is a practical way of knowing when the best time is to take advantage of the forage resource, as it influences the leaf area index which in turn will determine the leaf senescence of the lower stratum (Silva et al, 2016). In this regard, a study was carried out (Garay et al, 2019) and it was concluded that in Buffel grass forage production, environmental factors and regrowth age had a significant effect on the growth rate, which was reflected in the dynamics of forage yield and accumulation and the structural behavior of dry matter in Pennisetum ciliare cv. H-17 (Figure 8.1).…”
Section: Production and Nutritive Value Of Foragementioning
confidence: 99%